The Role of the Police in Eradicating Motor Vehicle Theft Cases at the Jambi Police Headquarters - Dwitama, Muhammad Yoga; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Motor vehicle theft (Curanmor) is a crime that disturbs the community and is economically detrimental. The role of the police is very vital in preventing and taking action against this case. Jambi Police have implemented various preventive and repressive strategies to reduce the number of Curanmor crimes. Although there has been a decrease in cases in recent years, internal and external challenges are still obstacles in eradicating this crime. This study aims to determine and analyze the role of the Jambi City Police (POLRESTA) in eradicating motor vehicle theft cases, identifying factors that are obstacles and solutions in eradicating motor vehicle theft cases in the jurisdiction of Jambi Police, strategies and efforts made by Jambi Police in increasing the effectiveness of eradicating motor vehicle theft cases as well as the obstacles and solutions implemented. The research method used is a sociological legal approach with data collection techniques in the form of literature studies, interviews, and documentation. The author analyzes the role of the Jambi City Resort Police (POLRESTA) in efforts to eradicate motor vehicle theft cases, factors that are obstacles and solutions in eradicating motor vehicle theft cases in the jurisdiction of the Jambi POLRESTA, strategies and efforts made by the Jambi POLRESTA in increasing the effectiveness of eradicating motor vehicle theft cases as well as obstacles and solutions applied. The role of the Jambi Police in eradicating motor vehicle theft is very strategic, covering the functions of law enforcement, protection, patronage, and public service. The main inhibiting factors include limited internal facilities and weak public awareness, which are overcome through increased synergy, services, and public education. Efforts made include preventive, repressive, and preemptive strategies, despite being faced with obstacles such as limited personnel, infrastructure, and low public participation. To overcome these challenges, the Jambi Police strengthens human resource capacity, establishes cross-sectoral cooperation, and utilizes information technology in case monitoring. The Jambi Police need to continue to improve the capacity and integrity of personnel through routine training, internal supervision, and expanding cooperation and technological modernization. The public is expected to actively participate in maintaining environmental security and implementing independent preventive measures, such as installing additional safety devices on vehicles. The local government and related agencies are also expected to provide budget support for strengthening police infrastructure and tightening vehicle administration to prevent data misuse by criminals.